Evidence of Carbon-Supported Porphyrins Pyrolyzed for the Oxygen Reduction Reaction Keeping Integrity - Tasca-Gottardo, F; Tasca-Gottardo, F; Zúñiga-Loyola, C; Zúñiga-Loyola, C (Nature Research, 2022)
Fe(III) 5,10,15,20-(tetraphenyl)porphyrin chloride (FeTPP) and Co(III) 5,10,15,20-(tetraphenyl)porphyrin chloride (CoTPP) were adsorbed on carbon Vulcan and studied as electrocatalysts for the oxygen reduction reaction (ORR) before and after pyrolysis. The pyrolysis process was also simulated through ab initio molecular dynamic simulations and the minimum energy path for the O2 dissociation after the interaction with the metal center of the FeTPP and CoTPP were calculated. After the pyrolysis the FeTPP showed the best performances reducing O2 completely to H2O with increased limiting current and lower overpotential. Tafel slops for the various catalysts did not change after the pyrolytic process suggesting that the mechanism for the ORR is not affected by the heat treatment. TEM images, X-ray diffraction, XPS spectroscopy, 57Fe Mössbauer, and DFT simulations, suggest that there is no breakdown of the macrocyclic complex at elevated temperatures, and that the macro cyclic geometry is preserved. Small variations in the Metal-O2 (M-O2) binding energies and the M–N bond length were observed which is attributed to the dispersive interaction between the macrocycles and the irregular surface of the Vulcan substrate induced by the heat treatment and causing better interaction with the O2 molecule. The theoretical strategy herein applied well simulate and explain the nature of the M–N–C active sites and the performances towards the ORR. © 2022, The Author(s).